Dead Bodybuilders Speaking from the Heart: An Analysis of Autopsy Reports of Bodybuilders That Died Prematurely - Guillermo Escalante; Dillon Darrow; V. N. Pradeep Ambati; Daniel L. Gwartney; Rick Collins (Journal of Functional Morphology and Kinesiology, 2022)
This study analyzed publicly available autopsy reports of male bodybuilders under the age of 50 who reportedly died from cardiovascular-related events. A general Google search with the terms “dead bodybuilders” was performed on 10 February 2022. Six reports were available for review and analysis. Bodybuilders had the following means: age (±SD) = 36 ± 7.1 years; height 1.82 ± 0.02 m; weight = 103.8 ± 5.3 kg; weight of heart = 575 ± 134.4 g; and left ventricular myocardium thickness (n = 3) = 16.3 ± 3.5 mm. The bodybuilders analyzed had a mean heart weight that is 73.7% heavier than the reference man (575 g vs. 332 g). Similarly, 100% of the autopsies reported left ventricular myocardium thickness of 16.3 ± 3.5 mm; this is 125% thicker than normative data for men. While abuse of AASs for prolonged periods of time may contribute to some of the cardiac abnormalities present in these bodybuilders, it should be noted that cardiac hypertrophy, including left ventricular hypertrophy, has also been reported in drug-free strength athletes. Each autopsy report included cardiovascular abnormalities within the cause of death. Association does not mean causation, but nonetheless bodybuilders should be aware of potential contributing cardiovascular risks with AAS abuse.